PLANNING AND CONTROLLING STATE AND CENTRAL GOVERNMENT GRANTS IN SELECTED STATE UNIVERSITIES OF GUJARAT: A FINANCIAL MANAGEMENT PERSPECTIVE - Chauhan, Anandkumar B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Higher education in Gujarat, India, has experienced significant growth driven by strategic government initiatives, robust infrastructure, and a focus on quality and innovation. This study examines the allocation and utilization of state and central government grants among selected state universities in Gujarat, highlighting the critical role of financial management in ensuring the effective use of these funds. Using secondary data from five prominent public universities over five years (2018–19 to 2022–23), the research employs ANOVA tests to identify significant differences in grant ratios relative to total income across universities. Results reveal statistically significant variations in both state and central government grant allocations, indicating non-uniform distribution among the institutions. The study underscores the importance of structured financial planning, robust monitoring, compliance mechanisms, and accountability frameworks to optimize fund utilization. Finally, the research proposes a strategic approach to planning and controlling government grants, emphasizing budget prioritization, real-time tracking, capacity building, transparency, and risk management, to enhance the sustainability and impact of higher education financing in Gujarat